2001
DOI: 10.1093/cercor/11.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Mechanisms of Attentional Control within the Human Prefrontal Cortex

Abstract: Neuropsychological tests that require shifting an attentional set, such as the Wisconsin Card Sorting Test, are sensitive to frontal lobe damage. Although little information is available for humans, an animal experiment suggested that different regions of the prefrontal cortex may contribute to set shifting behavior at different levels of processing. Behavioral studies also suggest that set shifting trials are more time consuming than non-set shifting trials (i.e. switch cost) and that this may be underpinned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
121
2
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(139 citation statements)
references
References 40 publications
12
121
2
2
Order By: Relevance
“…The present left inferior frontal activation was located more posterior at the junction of the precentral sulcus and the inferior frontal sulcus. Activation in this postero-ventral PFC region has been reported in a variety of tasks with rather different processing demands, including active maintenance [29], set shifting [10,35] or task preparation [3]. A common characteristic of these tasks is the requirement to learn new stimulus-response associations and to adapt them to current task demands [35].…”
Section: The Letter Taskmentioning
confidence: 99%
See 3 more Smart Citations
“…The present left inferior frontal activation was located more posterior at the junction of the precentral sulcus and the inferior frontal sulcus. Activation in this postero-ventral PFC region has been reported in a variety of tasks with rather different processing demands, including active maintenance [29], set shifting [10,35] or task preparation [3]. A common characteristic of these tasks is the requirement to learn new stimulus-response associations and to adapt them to current task demands [35].…”
Section: The Letter Taskmentioning
confidence: 99%
“…Activation in this postero-ventral PFC region has been reported in a variety of tasks with rather different processing demands, including active maintenance [29], set shifting [10,35] or task preparation [3]. A common characteristic of these tasks is the requirement to learn new stimulus-response associations and to adapt them to current task demands [35]. In fact, experimental lesion studies in animals showed that lesions in this area impair the relearning of stimulus-response and stimulus -reward associations [35,39] showed that activation in the postero-ventral PFC was not only enhanced in a set shifting task in which participants had to switch back and forth between a color and a shape matching task but also in a so-called reversal task in which only stimulus-response mappings were reversed.…”
Section: The Letter Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental in flexibility is one of the cognitive complaints experienced in mTBI14 and manifests as a tendency to perseverate or “become stuck.” The neural underpinnings of mental flexibility have been well studied using the Wisconsin Card Sort Task,29 and areas in prefrontal, frontal, and posterior cortical regions have been implicated using both fMRI30, 31, 32, 33, 34, 35, 36 and MEG 37, 38, 39. Our group has designed a simpler task aimed at probing the core “shifting” aspect of mental flexibility and we have optimized this for MEG 40…”
Section: Introductionmentioning
confidence: 99%